Pendidikan Kelas Ibu Hamil terhadap Peningkatan Pengetahuan Ibu Hamil di Wilayah Kerja Puskesmas Kotabaru Riau - Desysusanti, Desysusanti; Wati, Wati (Universitas Batanghari Jambi, 2024)
This research is a pre-experiment research with a one class pre test and post test design, in order to have an impact of class education for pregnant women on increasing maternal knowledge in one subject group of pregnant women in the Kotabaru Health Center work area, Riau. The secondary data for this research is data about the number of pregnant women at the Kotabaru Riau health center. The sample was 60 respondents. Data analysis used paired -t-test. The results of this study reveal that there is a correlation between the impact of class education for pregnant women on increasing the knowledge of pregnant women. The conclusion produced in this research is that there is a correlation between the educational impact of the Pregnant Mother Class application on increasing the knowledge of pregnant women in the work area of the Kota Baru Health Center, Riau in 2022.